The anthropology teaching in pedagogy courses: ways to diversity - Limonta Vieira, Karina Augusta [UNESP]; Badia, Denis Domeneghetti [UNESP] (Univ Estadual Sudoeste Bahia, 2015)
The article's aim is to conduct a discussion about contributions of the Anthropology to the courses in Pedagogy and the possibilities moving towards diversity whether curricular or looking the other. To realize a debate about teaching Anthropology courses in Pedagogy, it means, as appears Anthropology in Pedagogy courses, ending with the debate on Anthropology and Education, in order to elucidate the junctions of these areas, as well as the ways to cultural diversity. From the literature survey, in which evidence the question of theorizing of the courses of Pedagogy, and principally, of discipline Anthropology, moving away from the practice by both, I bring the survey carried in the E-Mec about the presence discipline of the Anthropology and Anthropology and Education in Pedagogy courses in the Paulista curriculum. From the survey, it notes that the disciplines are correlated to the six categories, such as: 1) Anthropology, 2) Anthropology and Education, 3) Sociology, Anthropology and Education, 4) Ethnic and Racial Relations, 5) Education and cultural diversity and, 6) Culture and Education. This survey realized leads us to discuss about the importance of the discipline Anthropology and its theories for the formation of Educators, so it is possible to think about the dialoge between Anthropology and Education, the barriers, and the possibility of looking for another, in order to valorize the cultural diversity. The article proposes a theorical broading of Education beyond the school.
Keywords: Anthropology; Pedagogy; Teaching; Diversity